The Development of Distribution Channel Strategies for Modern Retail Organizations - Nualsut, Samaporn; Promkum , Sujinda; Werasuk, Seksan (Journal of Roi Kaensarn Academi, 2024)
This quality research aims to: 1) study the development of distribution channels for modern retail organizations, 2) examine factors influencing the development of distribution channel strategies for modern retail organizations, and 3) develop multichannel distribution strategies for modern retail organizations. The sample group consists of eight participants, including retail managers and experts in the retail industry, who were selected using purposive sampling and snowball sampling methods. Data were collected through in-depth interviews, with the Critical Incident Technique (CIT) employed to gather insights from experienced individuals. The research instrument used was an interview form focused on the development of distribution channel strategies for modern retail organizations. The data were analyzed using content analysis. The findings revealed that distribution channel strategies for modern retail organizations comprise four key components: 1) analyzing customers, 2) developing strategy, 3) designing sales channels, and 4) implementation and evaluation. Based on these findings, it is recommended that retail organizations in Thailand collect and assess customer data from each sales channel to better understand customer needs. This approach will enable efficient management of a diverse marketing channel mix, thus enhancing the overall performance of modern retail organizations in the region.